Effects of the Two Oral Stimulations on Breast-Feeding Performance in Preterm Infants - Manprasert, Janjira; Wittayasooporn, Jariya; Daramas, Tipawan (Nursing Research and Innovation Journal, 2023)
It is interesting to find out dose of oral stimulation in preterm infants. This quasiexperimental research aimed to compare the breastfeeding performance of the preterm infants receiving the oral stimulation method I modified from Fucile and colleagues and those receiving the oral stimulation method II developed by Lessen. Each method had different doses in terms of duration and day. The breastfeeding performance is referred to breastfeeding behaviors, the amount of milk intake in the first 5 minutes, and the transitional duration from gavage to total oral feeding of the preterm infants. The sample consisted of 34 preterm infants born between 28 and 32 weeks of gestational age treated in the sick newborn units at two tertiary hospitals.They were selected by purposive sampling based on the inclusion criteria. They were equally divided into two groups by drawing lots without replacement. The sample with the odd numbers received oral stimulation method I once daily for 15 minutes, ten consecutive days. The sample with the even number received the oral stimulation method II once daily for 5 minutes, seven consecutive days. When the infants in each group finished receiving the oral stimulation program and the neonatal doctors allowed them to start breastfeeding, they were breastfed for 5 minutes,in the meantime their breastfeeding behaviors was observed by using the Preterm Infant’s Breastfeeding Behaviors Scale. The sample body weight change before and after breastfeeding was recorded to represent the amount of milk intake in the first 5 minutes, as well as the days transitional from gavage to target oral volume feeding were recorded. The data were analyzed using Mann-Whitney Test. It was found that the breastfeeding performance of the preterm infants between the two groups were not significantly different. Therefore, oral stimulation method II, developed by Lessen, was suggested in preterm infants born under 30 weeks of gestational age because it is a shorter procedure and less likely to disturb preterm infants. Keywords: Breastfeeding performance, Oral stimulation, Preterm infants